NEW METHODS FOR IMPLANT MATRIX FORMATION BASED ON ELECTROSPINNING AND BIOPRINTING TECHNOLOGIES - V. N. Vasilets; I. V. Kazbanov; A. E. Efimov; V. I. Sevastianov (Вестник трансплантологии и искусственных органов, 2009)
New implant materials for regenerative and replacement surgery based on biodegradable polymers like collagens and polyoxybutirates are developed. Porous structures with controllable morphology were formed from biodegradable polymers using electrospinning and bioprinting technologies. The matrixes were studied by visible and electron scanning microscopy as well as INTEGRA Tomo scanning probe platform making possible the restoration of inner 3D structure of polymer matrix.